2015
DOI: 10.1007/s11904-015-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Strategies for Scale up of Effective Combination HIV Prevention Interventions in Sub-Saharan Africa

Abstract: For the last three decades, sub-Saharan Africa has been the epicentre of the HIV epidemic. Some key drivers of the epidemic are specific to this region and there is an urgent need to develop context-specific strategies to reduce HIV-related burden. Implementation frameworks should endeavour to combine structural, behavioural and biomedical interventions and the future of the HIV response involves embracing different approaches for different populations; it is not 'one-size fits all approach'. Expanded use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For example, young people, who are a key priority group for HIV service delivery , often experience mobility events as they transition from school learner to job seeker. Further, their household composition can change significantly as caregivers move in and out of the home, particularly in households affected by HIV . Similarly, sub‐groups within geographic communities – including sex workers , truck drivers , and people living with disabilities – experience different household mobility patterns, which shape their HIV risk and access to services.…”
Section: Introductionmentioning
confidence: 99%
“…For example, young people, who are a key priority group for HIV service delivery , often experience mobility events as they transition from school learner to job seeker. Further, their household composition can change significantly as caregivers move in and out of the home, particularly in households affected by HIV . Similarly, sub‐groups within geographic communities – including sex workers , truck drivers , and people living with disabilities – experience different household mobility patterns, which shape their HIV risk and access to services.…”
Section: Introductionmentioning
confidence: 99%
“…To improve knowledge of HIV status, non-facility-based HIV testing approaches have been explored [5,6] and many are now integrated into community testing programmes [5,7–9]. Previous studies have shown high levels of competency in HIV testing amongst counsellors in household settings [10,11], and high levels of acceptance for community-based HIV testing are reported [5].…”
Section: Introductionmentioning
confidence: 99%
“…While political and social awareness regarding HIV/AIDS increases, effective and well-sustained implementation remains a looming challenge for both prevention and treatment. Bhardwaj et al, Williams et al, and Shaunabe and Bock all reference implementation challenges, explaining significant roadblocks in the deploy of effective Option B+ programs and early infant diagnosis (EID), patient monitoring and data collection, and implementation of combination prevention strategies, respectively [•2,•6,•25]. Bolton-Moore and Ciaraldi focus their presentation on the challenges and lessons learned from program expansion and scale-up, emphasizing the need for a sustainable chronic disease care management system for HIV [•5].…”
Section: The Continuum Of Carementioning
confidence: 99%
“…Observations of transmission risk correlating with plasma and genital viral load have translated into HPTN 052 clinical trial evidence of efficacy of ART in the infected partner preventing transmission to the HIV-uninfected partner [•9,•25,28-31]. Shanaube and Bock highlight how TasP has increased focus on the need to provide access to medications in a timely manner without treatment interruption due to drug stockouts, services to enhance access to testing and retention in care, and attention to highly vulnerable key populations, including adolescent and young women, persons in serodiscordant relationships, men who have sex with men (MSM), sex workers, and people who inject drugs (PWID) [23].…”
Section: Need For More Successful Hiv Preventionmentioning
confidence: 99%
See 1 more Smart Citation